Exerkines and Sarcopenia: Unveiling the Mechanism Behind Exercise-Induced Mitochondrial Homeostasis - Jiayin Wang; Dandan Jia; Zhiwang Zhang; Dan Wang (Metabolites)
Background/Objectives: Sarcopenia, characterized by the progressive loss of muscle mass and strength, is linked to physical disability, metabolic dysfunction, and an increased risk of mortality. Exercise therapy is currently acknowledged as a viable approach for addressing sarcopenia. Nevertheless, the molecular mechanisms behind exercise training or physical activity remain poorly understood. The disruption of mitochondrial homeostasis is implicated in the pathogenesis of sarcopenia. Exercise training effectively delays the onset of sarcopenia by significantly maintaining mitochondrial homeostasis, including promoting mitophagy, improving mitochondrial biogenesis, balancing mitochondrial dynamics, and maintaining mitochondrial redox. Exerkines (e.g., adipokines, myokines, hepatokines, and osteokines), signaling molecules released in response to exercise training, may potentially contribute to skeletal muscle metabolism through ameliorating mitochondrial homeostasis, reducing inflammation, and regulating protein synthesis as a defense against sarcopenia. Methods: In this review, we provide a detailed summary of exercise-induced exerkines and confer their benefit, with particular focus on their impact on mitochondrial homeostasis in the context of sarcopenia. Results: Exercise induces substantial adaptations in skeletal muscle, including increased muscle mass, improved muscle regeneration and hypertrophy, elevated hormone release, and enhanced mitochondrial function. An expanding body of research highlights that exerkines have the potential to regulate processes such as mitophagy, mitochondrial biogenesis, dynamics, autophagy, and redox balance. These mechanisms contribute to the maintenance of mitochondrial homeostasis, thereby supporting skeletal muscle metabolism and mitochondrial health. Conclusions: Through a comprehensive investigation of the molecular mechanisms within mitochondria, the context reveals new insights into the potential of exerkines as key exercise-protective sensors for combating sarcopenia.